Pengaruh Beban Kerja dan Self Efficacy terhadap Kinerja dengan Burnout sebagai Variabel Intervening pada Tenaga Kesehatan di RS Islam Faisal Makassar - Reni Angriani; Suhartini, Eka (Study of Scientific and Behavioral Management, 2024)
This study aims to examine the influence of workload and self-efficacy on performance with burnout as an intervening variable in health workers at the Islamic Faisal Hospital, Makassar. In this research, the variables used are workload and self-efficacy as independent variables, performance as the dependent variable, and burnout as the mediating variable. This research is quantitative research. The data source in this research comes from primary data, where the method for collecting data is using interviews and questionnaires which are distributed to all nurses at the Faisal Islamic Hospital in Makassar. The number of samples used was 110 samples. The data analysis technique in this research is using the Microsoft Excel computer program and your Statistical Product Service Solution (SPSS) version 26. The results of this research show that workload has a positive and significant effect on burnout, self-efficacy has a positive and significant effect on burnout, workload has an effect positive and significant effect on performance, self efficacy has a positive and significan effect on performance, workload has a positive and significant effect on performance mediated by burnout, self efficacy has a positive and significant effect on performance mediated by burnout. Keywords: Workload, Self Efficacy, Performance and Burnout